Study on medication adherence in patients with gestational diabetes mellitus complicated by postpartum glucose metabolism disorders based on the risk perception attitude framework - Zhou, Bing; Zhou, Zhuolin; Sun, Yu; He, Ting; Ge, Weihong; Sun, Lingjun; Ji, Cheng (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to assess the compliance with anti-hypoglycemic drugs among postpartum patients with gestational diabetes mellitus (GDM) through a questionnaire survey, and to examine the factors that may influence this adherence. The goal is to enhance pharmacists’ medication practices and improve glycemic control.MethodBased on the theory of risk perception attitude framework, the study selected pregnant women who delivered at Nanjing DrumTower Hospital’s obstetrics department from 2020 to 2022 and were diagnosed with GDM as the research subjects. The Morisky Medication Adherence Scale was used to evaluate their medication adherence. The correlation matrix was used to express whether there is a correlation between risk perception, self-efficacy, and medication adherence. Finally, a linear hierarchical regression model was used to present the moderating effect of self-efficacy on the relationship between risk perception and medication adherence.ResultsA total of 80 postpartum GDM patients receiving medication intervention were included in the study to assess medication adherence. The median score on the MMAS-8 scale was 3.75 (3.50, 5.50). The results of the Spearman test showed a positive correlation between GDM patients’ perception of future diabetes risk and postpartum medication adherence (r= 0.778, P<0.001). Additionally, self-efficacy was also positively correlated with medication adherence (r= 0.631, P<0.001). The results of the linear stratified regression model indicated that self-efficacy moderates the relationship between risk perception and medication adherence.ConclusionThe results of the MMAS-8 scale survey indicate poor medication adherence among postpartum GDM patients, with a significantly lower rate of good medication adherence compared to general T2DM patients. The stratified regression analysis demonstrates that risk perception and self-efficacy jointly influence postpartum medication adherence, and the risk perception attitude model can predict medication adherence among GDM patients postpartum.